(untitled) (Semiárida, 2023)
Biological collections are systematized repositories of some type of biological material that provide information on its identity and place of provenance at a given time. They record natural resource distribution and help understand biodiversity and its conservation. Most of those repositories are found in science museums, universities, research centers, and private collections. Particularly, palinotheques are reference collections of spores, pollen grains, and other palynomorphs - which include microscopic slides – all of which are of great importance for primary producers’ identification. The objective of this work was to organize, update, and classify the material of the palynological collection of the Agronomy College of the National University of La Pampa. Both the database and the physical material, including microscopic preparations, tubes with pollen residues, and envelopes with floral remains of herborized material, were organized and updated. These activities were completed in two collections: acetolized material (FALPPA) and fresh material (FALPPF). For the collection of acetolized material, 1382 preparations corresponding to 495 taxa and 79 botanical families were recorded. According to the taxa status, 75.2 % of the palynological preparations corresponded to native species of South America and 22.6 % to exotic species. Regarding the place of provenance, 92.3 % of the preparations came from La Pampa and 95.5 % of the departments of the province had specimens in the palinoteca, mainly Lihuel Calel with 712 preparations. According to the phytogeographic origin, 72 % corresponded to taxa of the Monte or shrubland, 23 % to the Espinal or Caldén´s forest, and the rest to the grassy steppe or Pampean Province. For the collection of fresh material, 68 families were recorded, including 161 genera, 97.8 % of them came from the Capital Department. The updating of the reference palinotheque, allowed us to organize the information and identify aspects of scientific importance, enhancing the value of one of the colleccions of the National University of La Pampa.